Is water in dental units microbiologically safe? - Michał Michałkiewicz; Dobrochna Ginter-Kramarczyk; Izabela K. Kruszelnicka (Nofer Institute of Occupational Medicine, 2015)
Background: Water supplied to the dental units must be of sufficient quality. The article presents the results of the microbiological analysis of cold municipal water which flows into a patient's disposable mouthwash cup, and demineralized water which flows through a waterline into the tool panel of a dental unit from the tank placed in the water group. Material and Methods: In order to assess the degree of purity (impurities) of water used in dental units, 2 series of microbiological tests were carried out in 6 dental surgeries from April to June, 2013. The water samples for microbiological testing were collected into sterile microbiological bottles in accordance with the current methodology. The water for the tests was collected from a sterile cup-filling tap (municipal water) and from an air/water syringe (demineralized water). The bacteria were cultured according to the Polish Standards - PN-EN ISO 6222, PN-EN ISO 9308-1, and PN-EN ISO 16266. Results: In the tested samples of water numerous psychrophilic bacteria (max 29 100 CFU/ml) and mesophilic bacteria (max 24 700 CFU/ml), including single coliforms, were found. Conclusions: The results show that water delivered to a dental unit should be periodically tested bacteriologically and in terms of physical and chemical properties. Water systems of dental units should also be periodically disinfected to eliminate bacteria and biofilm. Med Pr 2015;66(6):763-770